Haidilao customer evaluation based on Meituan data and analysis of the effectiveness of Haidilao’s sinking strategy ——Take Hohhot as an example - Chen, Lulu (Pacific International Journal, 2022)
This paper selects four Haidilao hotpot restaurants in Hohhot, Inner Mongolia, uses web crawler technology to obtain customer scores and comprehensive evaluations on taste, environment, service, cost performance, etc. on Meituan.com, and then uses text analysis methods to explore and analyze customers’satisfaction with dining in Haidilao hotpot restaurant, and put forward feasible suggestions for the implementation of Haidilao’s sinking strategy in Hohhot area.